Corpos femininos e o uso de crack: experiência, modos de subjetivação e agenciamentos. - Terto, Luisa de Marilak de Sousa (2019)
Because of its multifactorial nature, chemical dependence requires broad, integrated and differentiated care approaches, and in the light of this the present study aimed to understand the life experience of women users of crack in contemporary times. To deepen the understanding of different modes of female subjectivation is of fundamental relevance in thinking about reception practices that take into account the context and the demands of women who use crack. In this sense, this study is characterized as a qualitative research in which seven women were interviewed individually, in the age group from twenty-eight to thirty-seven years of age. All of the State of Pernambuco. We used as a method of data construction the History of Life (HV). We chose to make use of a narrative interview and also made use of a Field Diary, in which various experiences, observations and reflections were recorded throughout the data production process. As a strategy of analysis, we use discursive analytics of Foucaultian inspiration. The narratives of the interviewed women point out that it is impossible to understand the phenomenon of crack without having a look at the sociocultural and historical context of the subjects. The use of the analytical category of the genre is of extreme relevance for the understanding not only of the organic and physiological processes, but also of the discourses and knowledge that intertwine the experience of these women as users of crack. Therefore, we observe that in the processes of recognition of identities, the attributions of differences, which imply institutions of inequalities, of established hierarchies imbricated in the networks of power that circulate in a society are inscribed at the same time. The society in classifying the subjects, divides them assigning labels with the pretension to fix the identities. It defines, separates, and in different ways distinguishes and discriminates. This is what happens in our society, especially with women who use crack. In a broad social context, certain behaviors and practices are stimulated for men and inhibited for women. The gender norms to be transmitted from socialization reproduce hegemonic discourses about what it is to be a woman in a society that makes the view of women who use crack unfeasible, and brings an immeasurable problem to this part of the population that is on the margins of social exclusion. They are disregarded by public policies in general. They are considered by the power as unimportant, lives that should be corrected or that did not deserve to be lived, "abject bodies". It is concluded that the discourse on being a woman acts on them, producing ways of relating, if being, in a process of subjectivation that is agriculated by political, normative and cultural strategies. However, the life experience of women users of crack in the contemporaneity, is characterized as a complex phenomenon and not subject to causal and simplistic explanations. The subject presented here is active in his subjectivation process, producing modes of resistance and subversion that intend the disciplinary power of discourse on the woman who uses drugs.